Tribological properties of tin and bronze coatings electrodeposited from acid baths - Bengoa, Leandro Nicolás (2013)
Electrodeposited copper, tin and bronze are widely used as protective and decorative coatings due to their good corrosion resistance and appearance. However, there are some applications in which these properties are not enough and a low coefficient of friction is required. It is known that tin has a good lubricity and that this property depends on the morphology of the deposit. Furthermore some authors have reported the use of electroplated bronze as a lubricating coating in the oil industry. The bath commonly used for the electrodeposition of this alloy is a cyanide-based electrolyte which produces high quality deposits but has several environmental problems during use and disposal owing to its high toxicity. Many cyanide free baths have been developed, either acid or alkaline, but too little information about the performance of the resulting deposits have been reported. The aim of this work is to develop an acidic noncyanide electrolyte for the electrodeposition of high quality bronze coatings and evaluate their tribological behavior.